Imagining (In)Dependence: The United States and Philippine Freedom in the Age of Decolonization, 1945-1956 - Newbold, Elliot (2023)
This thesis explores how the Philippines constructed a postcolonial security relationship with their former colonizer, the United States, amidst the decolonization of Asia and the emergence of a “Third World.” It uses the vantage point of US-Philippine relations between 1945 and 1956 to demonstrate how a right-leaning neocolonial ally navigated the complex terrain between Cold War cooperation and conciliation with an emerging Afro-Asian bloc in order to chart its own course through the uneasy age of decolonization. Keen to protect and promote their postwar power, US policymakers saw the decolonization of the Philippines as a valuable weapon in the Cold War battle for colonised hearts and minds. Devastated by World War II and desperate to restore their control over the country, Philippine leaders championed their independence as a model for orderly democratic transition in exchange for protection and support. But Filipino elites had different priorities to their American counterparts. Philippine criticisms of inadequate aid, unequal treatment, and Washington’s reluctance to confront European colonialism pitted local concerns about self-determination against Cold War objectives such as countering communism. These conversations made an impression on other Third World leaders, who used their alliance as a cautionary tale about the dangers of Western assistance. By examining how Filipino elites created their own understandings of security, this thesis puts the Global South at the center to explore how the United States influenced and was influenced by, Philippine independence to project its understanding of decolonization to the Third World.